2011
DOI: 10.1016/j.neulet.2011.07.044
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of association between Val66Met polymorphism at BDNF gene and anxiety disorders in a community sample of children and adolescents

Abstract: Different lines of evidence support BDNF as a candidate gene in mood and anxiety modulation. More recently, the Met allele of the BDNF Val66Met polymorphism has been implicated in anxiety in animal models and anxiety-traits in humans. The aim of this study is to evaluate the a priori hypothesis that the association between anxiety disorders and Val66Met polymorphism at the BDNF gene would be replicated in a community sample of children and adolescents. 240 subjects from a total sample of 2457 children and adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…No association of BDNF Val 66 Met polymorphism has been found with anxiety disorders including generalized anxiety disorder (Surtees et al, 2007), panic disorder (Lam et al, 2004;Otowa et al, 2009;Shimizu et al, 2005) and post-traumatic stress disorder except in one community sample of children and adolescents (Tocchetto et al, 2011).…”
Section: Introductionmentioning
confidence: 85%
“…No association of BDNF Val 66 Met polymorphism has been found with anxiety disorders including generalized anxiety disorder (Surtees et al, 2007), panic disorder (Lam et al, 2004;Otowa et al, 2009;Shimizu et al, 2005) and post-traumatic stress disorder except in one community sample of children and adolescents (Tocchetto et al, 2011).…”
Section: Introductionmentioning
confidence: 85%
“…Previous study has found a strong correlation between BDNF methylation and BDNF val66Met polymorphism, which was shown to be associated with a number of psychiatric disorders (Neves-Pereira et al, 2005;Tocchetto et al, 2011;Verhagen et al, 2010) including AD (Lim et al, 2014). A further analysis showed there was significant ethnic difference in the frequency distribution of BDNF val66Met polymorphism among Asians, Caucasians and Africans (Fst > 0.15, Supplemental Table 1).…”
Section: Discussionmentioning
confidence: 83%
“…29 BDNF is a candidate gene in anxiety modulation. 30 The subject may be described as highly controversial.…”
Section: ■ Resultsmentioning
confidence: 99%
“…20 Finally, it should be noted that the Met allele of the BDNF Val66Met polymorphism has been implicated in anxiety in animal models. 30 The circadian-clock-related genes BCL2 and DRD2 were investigated in an association analysis to test whether they predispose to human anxiety disorders.…”
Section: ■ Resultsmentioning
confidence: 99%